Sustainable Process Design for Apple Pomace Based Biorefinery in the Agro-industry - Ruixue Wang; Zhiwei Li; Xiaoping Jia; Fang Wang (Chemical Engineering Transactions)
Biomass generated from agricultural processing residues has enormous energy potential and economic value. System analysis and design of a biorefinery using apple pomace as the main production feedstock was carried out. Three process pathways were designed (e.g., anaerobic fermentation, pyrolysis process, and value-added chemical products). A sustainability analysis for each process focused on its economic and environmental impact issues. Three pathways were modelled using Aspen Plus. The simulation results were used to determine yields and their investment feasibility and carbon footprint. Different perspectives may lead to different optimal pathways. The biorefining of apple pomace produces value-added products such as pectin, in addition to energy. These bioenergy sources can be used to replace fossil energy and are renewable, thus reducing CO2 emissions. Solutions are also proposed for pathways that are on the disadvantageous side.